2014
DOI: 10.4314/jab.v77i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de la qualité des cours d’eau de la ville de Taza utilisés dans l’irrigation des cultures maraîchères (Maroc).

Abstract: RÉSUMÉObjectif : Actuellement, le bassin versant de l'Oued Larbâa au Maroc se trouve menacé par une pollution intensive, vu l'énorme volume des rejets, sans aucun traitement préalable, de la ville de Taza. La pollution totale rejetée par la ville de Taza atteindra 30354 m 3 /j à l'horizon 2015 (RADEETA, 2004). L'utilisation agricole des eaux usées des affluents de l'oued Larbâa est plus intense et vise essentiellement les cultures maraîchères. Cette utilisation s'accompagne de risques sanitaires dont l'évaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have reported this form of contamination. For Koffi et al (2011) in Côte d'Ivoire, Abbou et al (2014) in Morocco and Holvoet et al (2014b) in Belgium, irrigation water from urban vegetable crops was the main source of microbial contamination of production. Coagulase positive Staphylococcus aureus has been reported in work in lettuce in Brazil (Cé sar et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported this form of contamination. For Koffi et al (2011) in Côte d'Ivoire, Abbou et al (2014) in Morocco and Holvoet et al (2014b) in Belgium, irrigation water from urban vegetable crops was the main source of microbial contamination of production. Coagulase positive Staphylococcus aureus has been reported in work in lettuce in Brazil (Cé sar et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…The selection of the chosen sites for this study is firmly grounded in a comprehensive foundation of previous research, particularly the extensive work conducted by Abbou et al (2014b). Moreover, a series of thorough field trips were undertaken to conduct a meticulous diagnosis of the study area.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…This drop in dissolved O2 concentration can be explained by the proliferation of microorganisms following the high biodegradable organic load, especially at point O4 characterized by a high BOD 5 (Fig. 8) located downstream of the uncontrolled public landfill (the Julien landfill) (Abbou et al 2014a). The increase in dissolved oxygen concentration during the winter and spring periods is due to the decrease in temperature because the lower the temperature more biological activity decreases are O2 consumption also decreases (Edberg et al 2000).…”
Section: Parameters Measured In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic structure which is progressively increasing on the one hand and the evolution of the gross domestic product per capita has generated a massive production of solid waste (El Hammoudani, 2019, Abbou, 2020, Fernine, 2022. In this context, the production of leachate, which is one of the main consequences, remains one of the threats to the environment (Coffin, 2022), especially to water resources (El Hammoudani, 2021, Benaissa, 2022, Bouhout, 2022) (soil pollution, contamination of groundwater and surface water) (Abbou, 2014, Abbou et al, 2020, Al Raisi, 2022, which could have negative health effects on the population (Fekri, 2012.…”
Section: Introductionmentioning
confidence: 99%